Childhood adversity is associated with left basal ganglia dysfunction during reward anticipation in adulthood - Dillon, Daniel G. (2009)
BACKGROUND: Childhood adversity increases the risk of psychopathology, but the neurobiological mechanisms underlying this vulnerability are not well-understood. In animal models, early adversity is associated with dysfunction in basal ganglia regions involved in reward processing, but this relationship has not been established in humans. METHODS: Functional magnetic resonance imaging was used to examine basal ganglia responses to (a) cues signaling possible monetary rewards and losses, and (b) delivery of monetary gains and penalties, in 13 young adults who experienced maltreatment before age 14 and 31 non-maltreated controls. RESULTS: Relative to controls, individuals exposed to childhood adversity reported elevated symptoms of anhedonia and depression, rated reward cues less positively, and displayed a weaker response to reward cues in the left globus pallidus. There were no group differences in right hemisphere basal ganglia response to reward cues, or in basal ganglia response to loss cues, no-incentive cues, gains, or penalties. CONCLUSIONS: Results indicate that childhood adversity in humans is associated with blunted subjective responses to reward-predicting cues as well as dysfunction in left basal ganglia regions implicated in reward-related learning and motivation. This dysfunction may serve as a diathesis that contributes to the multiple negative outcomes and psychopathologies associated with childhood adversity. The findings suggest that interventions that target motivation and goal-directed action may be useful for reducing the negative consequences of childhood adversity.